Isolation and Identification of Endophytic Bacteria Producing IAA and Phosphate Solubilizers from Mangrove Roots in the Bagek Kembar Sekotong Area and In Vitro Testing on the Germination of Vigna radiata L. - Havizah, Ilma Nur; Zulkifli, Lalu; Rasmi, Dewa Ayu Citra; Sedijani, Prapti (Jurnal Biologi Tropis, 2025)
Mangroves are a potential source of plant growth-promoting bacteria (PGPB) due to their unique habitat. Exploring potential endophytes as biofertilizers to reduce dependence on chemical fertilizers. This study aims to determine the effect of IAA-producing endophytic bacteria and phosphate solubilizers from mangrove roots on the germination of mung beans (Vigna radiata L.). The bacteria were isolated from mangrove roots in the Bagek Kembar Mangrove Ecosystem Area, Sekotong, West Lombok. The study began with the isolation of endophytic bacteria, followed by characterization, including morphological identification, cell morphology (via Gram staining), and physiological properties (biochemical testing). The potential of endophytic bacteria to produce IAA was tested qualitatively (using colorimetry) and quantitatively (using a spectrophotometer at a wavelength of 530 nm). Additionally, the ability of endophytic bacteria to solubilize phosphate was tested both qualitatively (using a screening method) and quantitatively (using a spectrophotometer at a wavelength of 880 nm). To test the effect of endophytic bacteria on soybean germination, green soybean seeds were grown on modified Murphy medium for 5 days, with the observed parameters being plant height, root length, fresh weight, and dry weight. The results of the green soybean germination observations were analyzed using One-Way ANOVA. Based on the research results, 11 endophytic bacterial isolates were found to be capable of producing IAA in the range of 16.88 to 30.28 ppm. Meanwhile, in terms of phosphate solubility, based on the screening results, 6 out of 11 isolates were able to solubilize phosphate with an average dissolved phosphate concentration of 17.63 ppm on the 4th day of incubation. The results of the analysis of the effect of IAA-producing bacteria and phosphate solubilizers on the germination of green beans showed a significant effect on plant height, root length, fresh weight, and dry weight of green bean plants.